Self-consistency equations for nonunitary phases of superfluid Fermi liquid with spin-triplet pairing in a magnetic field - Tarasov, A.N. (Вопросы атомной науки и техники, 2001)
The generalized Fermi-liquid approach is used (with taking into account of the spin-exchange Fermi-liquid interaction) for description of different nonunitary phases of neutral paramagnetic superfluid Fermi liquid (SFL) with spin-triplet pairing of the ³He type (and also for the dense superfluid pure neutron matter (SNM) existing inside core of neutron stars) in a strong magnetic field. In particular, the systems of connected nonlinear integral equations for the order parameter and effective magnetic field are obtained on the basis of energy functional (with Landau exchange amplitudes F₀a≠0 and F₂a≠0 ) which is quadratic in distribution functions of quasiparticles for nonunitary phases of ³He - A₂ type for SFL (or SNM) in a strong static and uniform magnetic field at any temperatures 0 ≤ T ≤ Tc (Tc is the normal - superfluid transition temperature).